APOLOGY STRATEGY IN DISNEY AND PIXAR’S LUCA MOVIE: A PRAGMATIC APPROACH - SILVINA SILVINA; RITA HARTATI (LINGUISTICA, 2023)
This paper aims to analyse the various apology strategies used by the characters in the Luca movie script and describe their use through a pragmatic approach by referring to the theory of Klimczak and Pawlak (2014) and Fraser's theory (1981) to explain the factors that influenced the use of apology strategies by characters in Luca's film script. This study uses a descriptive qualitative research method with data obtained from the film script Luca. The results of this study indicate that there are 23 utterances featuring apologies made by 6 characters in Luca's story. The findings are grouped into a taxonomy of apology strategies, there are 9 types of apology strategies used by the characters in Luca's story. The 9 types of strategy include Illocutionary Force Indicating Device (an expression of regret) of 5 utterances, Illocutionary Force Indicating Device (a request for the forgiveness) of 1 utterance, Phatic Communication of 2 utterances, Acknowledgement of Responsibility (explicit self-blame) of 2 utterances, Internal Intensifiers (intensifying adverbials) with 2 utterances, Acknowledgement of Responsibility with 4 utterances of lack of intent, Acknowledgement of Responsibility (expression of embarrassment) with 4 utterances, Explanation or account of the situation with 2 utterances, and Acknowledgement of Responsibility (refusal to acknowledge guilt) with 1 utterance, which every utterance and strategy were influenced by 1-2 factors.